Pathological fractures of distal tibia and fibula with a parathyroid adenoma: A rare case report and review of literature - Smruti Srinivasan; Abhishek Kumar Rai; Caroline Thomson; Ajay Naidu (Journal of Orthopaedic Reports, 2022)
Background: Primary hyperparathyroidism may mimic osteoporosis and lead to pathological fractures. Case report: We report a case of 35-year-old female who sustained left distal tibia-fibula fracture after a trivial fall, later diagnosed to have left inferior parathyroid adenoma. The fracture was managed conservatively and left inferior parathyroidectomy for the adenoma. At four years follow-up, there are no clinical or biochemical signs of recurrence. Conclusion: Pathological fracture in a case of parathyroid adenoma is extremely rare and require a multidisciplinary approach for optimal outcome. A combination of clinical, biological, radiological and biochemical markers with a high index of suspicion in an isolated bone fracture is required to diagnose parathyroid adenoma.